The multi-representational ability profile of physics students in the interactive multimedia assisted problem-based learning during the Covid-19 pandemic - Masrifah Masrifah; Dewi Amiroh (Universitas PGRI Kanjuruhan Malang, 2023)
This study aims to analyze the multi-representation ability profile of physics students in the interactive multimedia assisted problem-based learning during the Covid-19 pandemic. This research is a qualitative descriptive study. This research involved 9 female teachers and 1 male teacher. Data on the multi-representation abilities of Physics teachers were obtained by using the 5 item multi-representation problem instrument in the form of representing image to verbal, verbal to mathematics, verbal to picture, table to graph, and mathematics to verbal. Meanwhile, researchers utilized interviews to gather information on the difficulties that prospective physics teachers had in working on multi-representational problems. The results of the analysis show that the multi-representation ability of prospective physics teachers is generally good. This can be seen from the average percentage obtained by 63%. However, there are two indicators that are still not good, namely verbal to mathematics representation and mathematics to verbal representation with an average percentage of 30% and 43% respectively. For this reason, it is necessary to make efforts to increase the multi-representational abilities of prospective physics teachers by using approaches, teaching materials, and learning media that are able to teach and present physics concepts in various forms of representation so that it is easier to understand the concepts presented.